Barriers and Strategies of School Public Relations Management in Building Institutional Image and Public Trust: A Systematic Literature Review - Reza Ifnuari; Robby Haryanto (Jurnal Manajemen Pendidikan, 2025)
Background In an increasingly competitive educational environment, schools are required to build a strong institutional image and maintain public trust. School public relations (PR) management plays a strategic role in shaping positive perceptions; however, many institutions still encounter structural and operational barriers that hinder effective implementation. Purpose This study aims to examine the strategies employed in school public relations management to strengthen institutional image and public trust, as well as to identify the key challenges that influence their effectiveness Method a qualitative approach was adopted using a Systematic Literature Review (SLR). The literature search was conducted systematically through Publish or Perish, focusing on articles published between 2021 and 2025. The selection process followed the PRISMA framework, encompassing identification, screening, eligibility, and inclusion stages. Fifteen relevant articles were selected and analyzed in depth Results The findings reveal that effective PR strategies include optimizing social and mass media, strengthening stakeholder relationships, communicating flagship programs, and developing brand image and awareness. Nevertheless, implementation is constrained by limited human resources, low digital competencies, budget restrictions, negative public perceptions, and weak internal coordination and organizational support Contribution/value This study highlights that successful school public relations management relies not only on communication strategies but also on adequate resources, strong organizational support, and proactive leadership to ensure professional and sustainable PR practices